2014
DOI: 10.1007/s10461-014-0763-6
|View full text |Cite
|
Sign up to set email alerts
|

Individualised Motivational Counselling to Enhance Adherence to Antiretroviral Therapy is not Superior to Didactic Counselling in South African Patients: Findings of the CAPRISA 058 Randomised Controlled Trial

Abstract: Concerns that standard didactic adherence counselling may be inadequate to maximise antiretroviral therapy (ART) adherence led us to evaluate more intensive individualised motivational adherence counselling. We randomised 297 HIV-positive ART-naïve patients in Durban, South Africa, to receive either didactic counselling, prior to ART initiation (n=150), or an intensive motivational adherence intervention after initiating ART (n=147). Study arms were similar for age (mean 35.8 years), sex (43.1% male), CD4+ cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…9–31,93 Two of the studies reported mortality as an outcome, 9,10 22 reported morbidity, 930 1 on retention in care, 19 2 on quality of life, 15,20 and 1 on prevention of HIV transmission, 31 with some studies reporting on multiple outcomes. One article included information on the costs associated with providing adherence counseling and support.…”
Section: Resultsmentioning
confidence: 99%
“…9–31,93 Two of the studies reported mortality as an outcome, 9,10 22 reported morbidity, 930 1 on retention in care, 19 2 on quality of life, 15,20 and 1 on prevention of HIV transmission, 31 with some studies reporting on multiple outcomes. One article included information on the costs associated with providing adherence counseling and support.…”
Section: Resultsmentioning
confidence: 99%
“…Study designs were of variable quality and generally showed mixed or positive results for well-being and depressive symptoms indicators. In the literature, psychosocial support interventions were primarily designed and evaluated with regard to instrumental outcomes, such as care engagement (Wanyenze et al, 2011), medication adherence (Cook, Carrington, Schmiege, Starr, & Reeder, 2015;van Loggerenberg et al, 2015), sexual risk reduction (Echenique et al, 2013;Klein et al, 2013;Morin et al, 2007;Wingood et al, 2004), and disclosure (Mundell et al, 2011). No studies measured SRH decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…16 The Current Study Data for this qualitative study were collected as part of a randomized control trial (RCT), CAPRISA 058, which aimed to test the efficacy of an individualized motivational counseling intervention to enhance ART adherence. 27 We conducted this RCT in response to concerns that, due a lack of political support for HIV treatment and, more damagingly, explicit support of nutritional supplements, vitamins, and other means of 'treating' HIV, [28][29][30] patients may believe that that ART was no better than these 'treatments' or even poisonous. 31 The majority of our participants were also enrolled on a programme to integrate HIV and tuberculosis (TB) treatment, since active TB is often a common entry point for HIV testing and ART initiation.…”
Section: Introductionmentioning
confidence: 99%
“…In response to these concerns, an enhanced adherence support intervention was developed (described in the parent study 27 ). The primary study showed that the participants who received enhanced adherence support had no greater virological suppression at 9 months than the control arm participants (87.9% vs. 89.8%, p = 0.62).…”
Section: Introductionmentioning
confidence: 99%